Identification of new religious movements in Belarusian science - Martinovich, Vladimir A. (Journal of the Belarusian State University. Sociology, 2023)
This article is devoted to the analysis of the process of identification of new religions in Belarusian science. Based on a representative sample of 798 published works by scientists dealing with the topic of new religious movements, the following are analysed: the institutionally determined specificity of scientists’ reactions to the phenomenon of non-traditional religiosity; the distribution of subjects of identification of new religions by scientific disciplines; the configuration of religious organisations identified by scientists in the Republic of Belarus in the period from 1988 to 2020. Special attention is paid to the identification of sectors of the confessional milieu of Belarus that are not covered by the attention of scientists, the analysis of the structural and substantive characteristics of new religions that fall into the focus of scientists’ attention. A number of promising areas of analysis of the stated topic are clarified, as well as its significance for the development of a comprehensive model of society’s reactions to non-traditional religiosity. The social identification of religious organisations with one of the types of religiosity is among the most significant indicators of the reaction of social institutions to religious diversity. Different institutions of society identify different configurations of new religious movements in accordance with their internal norms and standards for evaluating the confessional milieu.